Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Garuda Plaza Hotel Medan - Muhammad Chaidir; Aswin Akbar (CIVITAS: Jurnal Studi Manajemen, 2022)
The research was conducted at Garuda Plaza Hotel Medan. The purpose of this study is to find out the level of motivation, the level of work discipline, the level of performance of hotel employees,as well as whether there is an influence of motivation and work discipline on the performance of Garuda Plaza Hotel Medan employees both partially and simultaneously. the research method used is deskriptif quantitative method. Furthermore, data collection techniques are used by disseminating questionnaires,interviews, and observations. The data analysis technique used is double-digit linear regressionanalysis. based on the analysis of respondents' answers, the results were obtained that the level of motivation and level of employee discipline had a positive and significant effect. While the level of employee performance is in the category of positive and significant influence. The results of this study show that: there is an influence of motivation and work discipline on the performance of Garuda Plaza Hotel Medan employees both partially and simultaneously.